2008
DOI: 10.1089/aid.2008.0130
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism, Recombination, and Mutations in HIV Type 1gag-Infecting Peruvian Male Sex Workers

Abstract: HIV genetic diversity in female sex workers (FSW) has been previously described in Peru; however this information is not yet available for male sex workers (MSW). Therefore, purified peripheral blood mononuclear cell DNA from 147 HIV-infected subjects identified as MSW and FSW was used to amplify a 460-bp fragment corresponding to the p24-p7 region of the gag gene. The PCR product was digested with restriction enzymes to identify genetic polymorphism. Later, a random group of samples (n = 19) was sequenced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…26 In this study, subtype C was detected in an Argentinean patient (Dr. La Rosa, personal communication, 2011) who represents the first recorded imported case in Peru. Of interest, evidence of B/C recombination reported previously 8 and in this article suggests that this finding does not necessarily represent an isolated case. A program of continued subtype surveillance is necessary, especially in border areas with Brazil, in order to determine additional cases of subtype C in this country.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…26 In this study, subtype C was detected in an Argentinean patient (Dr. La Rosa, personal communication, 2011) who represents the first recorded imported case in Peru. Of interest, evidence of B/C recombination reported previously 8 and in this article suggests that this finding does not necessarily represent an isolated case. A program of continued subtype surveillance is necessary, especially in border areas with Brazil, in order to determine additional cases of subtype C in this country.…”
Section: Discussionsupporting
confidence: 60%
“…7 The high frequency of subtype B was persistent in Peruvian populations regardless of their sexual behavior and epidemiologic characteristics. 5,8,9,20 This information suggests that subtype B has gained important epidemiologic success in this country in contrast to other subtypes previously identified such as A and F. 7,9,21 In this work we have identified cases of subtypes A, C, and H (n = 4). In regard to subtype A, there is only one case reported in South America from a Peruvian heterosexual male patient, 7 who denied having had sexual contact with any individuals from other countries.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…20 In a study published in 2005, Castro et al 20 observed that 2 (1 pure, one recombinant) out of 106 cases from Venezuela had C subtype sequences, suggesting a proportion of HIV-1C larger than the one observed in Argentina by one order of magnitude. In a study performed in Peru, Yabar et al 62 observed that 1 out of 19 randomly taken samples was a B=C recombinant, also suggesting the circulation of HIV-1C strains in this country. Thus, our sample might be too small to yield conclusive results.…”
Section: Discussionmentioning
confidence: 92%